Comparative Evaluation of Single Fixed Dosing and Weight‐Based Dosing of Rasburicase for Tumor Lysis Syndrome. Issue 3 (1st March 2013) - McBride, Ali; Lathon, Sherrie C.; Boehmer, Leigh; Augustin, Kristan M.; Butler, Sara K.; Westervelt, Peter
<x xml:space="preserve">Abstract</x> Study Objective To evaluate single fixed dosing versus weight‐based dosing strategies for rasburicase to determine the minimum dose required to mitigate hyperuricemia in the treatment or prevention of tumor lysis syndrome. Design Retrospective medical record review Setting Academic medical center Patients A total of 373 patients with a diagnosis of a hematologic malignancy or solid tumor and who received at least one dose of rasburicase over a 6‐year period between January 1, 2005, and February 18, 2011; 180 patients received single doses of 3 mg (38 patients), 6 mg (99 patients), or 7.5 mg (43 patients), and 193 patients received weight‐based dosing. Measurements and Main Results Tumor lysis syndrome laboratory data were recorded at baseline and monitored up to 72 hours after initial rasburicase administration. Median baseline plasma uric acid levels were 6.85 mg/dl, 8.80 mg/dl, 8.00 mg/dl, and 9.20 mg/dl, respectively, in the 3‐mg, 6‐mg, 7.5‐mg, and weight‐based dosing groups. Treatment success was defined as a normalized plasma uric acid level (< 7.5 mg/dl) within 24 hours after receiving rasburicase. The mean weight‐based dose was 0.16 mg/kg. Six rasburicase treatment failures occurred; two were in the 3‐mg group, one was in the 6‐mg group, and three were in the weight‐based dosing group. At 24 hours after rasburicase administration, no statistically significant differences in treatment success were noted among groups (92.9% vs 97.6% vs 100.0% vs 98.0% in the 3‐mg, 6‐mg, 7.5‐mg, and weight‐based dosing groups, respectively, p=0.1238). Conclusion The efficacy of all single fixed doses and weight‐based dosing strategies evaluated in this study appear to be comparable in normalizing plasma uric acid levels within 24 hours of rasburicase administration. Although use of a 3‐mg rasburicase dose may be the most cost‐effective treatment strategy in managing hyperuricemia secondary to tumor lysis syndrome, the 6‐mg dose resulted in lower sustained uric acid levels after rasburicase administration. Further analysis of patient specific factors contributing to the need for repeat rasburicase administration should be conducted in larger, prospective clinical trials.